Jual Beli Akad Mu’atah pada Kantin Kejujuran - Ita Dwilestari (CV. Creative Tugu Pena, 2024)
In the practice of buying and selling at the UMALA honesty canteen, that is, if the seller is not found on the spot, in practice the buyer takes the goods that have been provided by the seller, then the buyer pays by putting money in the box that has been provided, and the buyer also takes his own change. Therefore, in the practice of buying and selling in the honesty canteen, no contracts were found. Based on the background above, it can be formulated. First, what are the buying and selling practices in the UMALA honesty canteen? Second, whether the honesty canteen practices at UMALA are in accordance with the system mu'athah? This research is a type of field research, where the research object is focused on buying and selling practices in the UMALA honesty canteen. The nature of this research is descriptive-analytic, where the researcher tries to describe and analyze the buying and selling process in the honesty canteen, namely by referring to the concept buy and sell mu'athah. Data collection by going directly into the field is collected through observation, free question and answer (interview), and documentation. Meanwhile, in analyzing data, researchers used qualitative analysis. The results of this research show that first, the practice of buying and selling begins with students who are more interested in buying things at close range without having to go to the canteen, with the honesty canteen itself as an object that provides several types of snacks. Students only need to take the snacks they want and pay for them by putting the money in the payment box provided, and if there is change, the buyer takes the change himself. Second, the practice of buying and selling in the honesty canteen when viewed from a buying and selling perspective muathah, this practice is still declared legal, because of the concept of buying and selling mu'athah There are still buyers and sellers. It's just that there is no statement of buying and selling or any statement (consent or acceptance) from either of them (using a handover of something purchased or one of the parties stating that they are buying or selling).